2016
DOI: 10.1038/srep37850
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive Profile of Levo-tetrahydropalmatine in Acute and Chronic Pain Mice Models: Role of spinal sigma-1 receptor

Abstract: We have recently reported that repeated systemic treatments of extract from Corydalis yanhusuo alleviate neuropathic pain and levo-tetrahydropalmatine (l-THP) is one of active components from Corydalis. We designed this study to investigate antinociceptive effect of l-THP in acute and chronic pain models and related mechanism within the spinal cord. We found that intraperitoneal pretreatment with l-THP significantly inhibited the second phase of formalin-induced pain behavior. In addition, intrathecal as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…Consistent with our result, SNI CD-1 mice exhibited abnormal CatWalk ™ -duration of standing, paw intensity and print area in the ipsilateral hindpaw [ 56 ]. In another neuropathic pain model, the CCI model, CatWalk ™ explored aberrant coordination, intensity and area data [ 13 , 17 , 57 59 ], and the alterations in coordination and intensity correlated with punctate allodynia [ 58 ]. Compared to CCI, SNI includes complete ligations and incisions of the tibial and common peroneal nerves, and therefore induces irreversible manifestations due to motor nerve injury, for instance, the flexed ipsilateral hindpaw resulting in reduced area data.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our result, SNI CD-1 mice exhibited abnormal CatWalk ™ -duration of standing, paw intensity and print area in the ipsilateral hindpaw [ 56 ]. In another neuropathic pain model, the CCI model, CatWalk ™ explored aberrant coordination, intensity and area data [ 13 , 17 , 57 59 ], and the alterations in coordination and intensity correlated with punctate allodynia [ 58 ]. Compared to CCI, SNI includes complete ligations and incisions of the tibial and common peroneal nerves, and therefore induces irreversible manifestations due to motor nerve injury, for instance, the flexed ipsilateral hindpaw resulting in reduced area data.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, tetrahydropalmatine, a natural alkaloid from Corydalis genus Yanhusuo, has been used for the treatment of chronic pain for decades [11]. In this study, we report the potent antinociceptive effects of a natural product and TRPM 3 blocker, isosakuranetin ([2S]-5,7-dihydroxy-2-[4-methoxyphenyl]-2,3-dihydrochromen-4-one; Fig.…”
Section: Introductionmentioning
confidence: 95%
“…Besides, brucine, koumine, gelsenicine [26], and isorhynchophylline [103] inhibited CCI-induced thermal hyperalgesia. It is reported that matrine [95], levo-tetrahydropalmatine [98], berberine [99], and sinomenine [97] could not affect the ability of spontaneous activity and motor coordination of CCI mice. In other words, these alkaloids did not induce sedation in CCI mice.…”
Section: Effects Of Alkaloids On Sciatic Nerve Chronic Constriction Imentioning
confidence: 94%
“…Alkaloids matrine [95] reduced among mechanical allodynia, cold allodynia, and thermal hyperalgesia, whereas guanfu base A [96] reduced mechanical and thermal hyperalgesia. Sinomenine [97], levo-tetrahydropalmatine [98], berberine [99], brucine [100], dehydrocrenatidine [101], koumine [102] and isotalatizidine [25] reduced mechanical allodynia. Besides, brucine, koumine, gelsenicine [26], and isorhynchophylline [103] inhibited CCI-induced thermal hyperalgesia.…”
Section: Effects Of Alkaloids On Sciatic Nerve Chronic Constriction Imentioning
confidence: 98%